Data literacy : the essential language in the digital era - Law, Sau Wai; Yim, Benny (Routledge, 2026)
Data has been called the 'new oil' of the 21st-century economy, yet knowledge of how to harness and comprehend data is lagging. This book presents a comprehensive guide for university students and business practitioners to acquire the core competencies to become data literate.Data Literacy: The Essential Language in the Digital Era introduces a logical way to master the nature, features, characteristics, limitations, uses, and protection of data, as well as its legal, regulatory, and ethical concerns. The book helps readers to develop their data literacy skills, based on lessons learnt from the authors' professional experience in the banking and education sectors, together with doctrinal and empirical findings from research and observation.With a structured methodology for interpreting data, practical case studies, and useful exercises, this textbook is an essential guide and reference for students, practitioners, and scholars in any discipline, as well as policymakers and regulators from all over the world.
Keywords: Data mining.; Research -- Data processing.; Quantitative research.; Information literacy.; elektronické knihy; electronic books